Influence of the Niii/Mniiratio on the Physical Properties of Heterometallic Ni2xmn(2−2x)P2s6phases and Potassium Intercalates K0.8ni2xmn(1.6−2x)P2s6·2h2o - Aliaga-Vidal, C; Aliaga-Vidal, C (Royal Society of Chemistry, 2021)
Bimetallic Ni2xMn2−2xP2S6phases, where 2X= 0.4 (Ni0.4), 0.8 (Ni0.8) and 1.2 (Ni1.2), were synthesized by a microwave assisted method, starting from the corresponding potassium intercalates K0.8Mn1.6P2S6·2H2O, K0.8Ni0.4Mn1.2P2S6·2H2O, and K0.8Ni0.8Mn0.8P2S6·2H2O. The magnetic, optical, and electrical properties were recorded, in order to visualize the influence of the secondary nickel(ii) ions on the physical properties of the pristine Mn2P2S6phase. Both dc susceptibility and EPR data show that the antiferromagnetic interactions are attenuated in the layers of the bimetallic phases, while the critical temperature remains constant (ca.80 K) for all the bimetallic phases, similar to that of Mn2P2S6. Conversely, the absorption edge of the solid state UV-visible spectra shifted to lower energies as the percentage of nickel(ii) increased, tending to that of the band gap value of the pristine Ni2P2S6phase. Moreover, the electric conductivity ofNi0.4was similar to that of the pristine Mn2P2S6phase, while that ofNi0.8andNi1.2approached the values of the electric conductivity of the pristine Ni2P2S6phase. On the other hand, the potassium intercalates K0.8Mn1.6P2S6·2H2O and K0.8Ni0.4Mn1.2P2S6·2H2O showed magnetization at 16 K, the latter being much weaker as compared to the first. The detrimental effect of the secondary nickel(ii) ions in the layers of the bimetallic phases became evident for K0.8Ni0.8Mn0.8P2S6·2H2O, where the magnetization at low temperatures was not observed. The absorption edge shifted to higher energy values for K0.8Mn1.6P2S6·2H2O and K0.8Ni0.4Mn1.2P2S6·2H2O, as compared to Mn2P2S6andNi0.4, respectively, but the value remained close to that of Ni2P2S6for K0.8Ni0.8Mn0.8P2S6·2H2O. InNi0.8andNi0.4, the electrical conductivity at low frequencies stems from polarization processes such as Maxwell/Wagner/Sillars electrode polarization. Moreover, an additional polarization process is observed in the intercalates because K+ions in the interlayer act as charge transport carriers. Consequently, the interacalates present higher electrical conductivity compared with the pristine Mn2P2S6phase, by a factor ofca.102 © The Royal Society of Chemistry and the Centre National de la Recherche Scientifique 2021.